2005
DOI: 10.1111/j.1467-9221.2005.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Voluntary Associations: Relations with Resources, Personality, and Political Values

Abstract: Participation in voluntary associations is explained by different theories in sociology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
303
1
27

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(355 citation statements)
references
References 44 publications
24
303
1
27
Order By: Relevance
“…However, they may also have a greater opportunity cost of time (Wilson, 2000). Whilst, empirically, the literature has found a positive relationship (Freeman, 1997;Bekkers, 2005;Huang, Van Der Brink, & Groot, 2009), studies analysing the causal relationship have reported no significant relationship and, in some cases, have found a negative one (Gibson, 2001;Dee, 2004;Denny, 2003). Previous literature focusing on skills suggests that highly-skilled individuals in most countries are more likely to participate in voluntary activities, even when controlling for education.…”
Section: Literature Review Of the Relationship Bet Ween Education mentioning
confidence: 88%
“…However, they may also have a greater opportunity cost of time (Wilson, 2000). Whilst, empirically, the literature has found a positive relationship (Freeman, 1997;Bekkers, 2005;Huang, Van Der Brink, & Groot, 2009), studies analysing the causal relationship have reported no significant relationship and, in some cases, have found a negative one (Gibson, 2001;Dee, 2004;Denny, 2003). Previous literature focusing on skills suggests that highly-skilled individuals in most countries are more likely to participate in voluntary activities, even when controlling for education.…”
Section: Literature Review Of the Relationship Bet Ween Education mentioning
confidence: 88%
“…Because formal volunteering often requires extensive social interactions, scholars have posited that it is associated with being extraverted (Burke & Hall, 1986). Several studies have observed a significant association between extraversion and volunteering (Bekkers, 2005;Burke & Hall, 1986;Carlo et al, 2005;Herzog & Morgan, 1993), but see Trudeau and Devlin (1996) for an exception.…”
Section: The Mediational Model Extraversionmentioning
confidence: 99%
“…Although Francis and Bolger (1997) failed to find an association between extraversion and church-related involvement, we reasoned that extraverted older adults may be more likely than introverted older adults to manifest their religiosity by attending church and participating in church-sponsored activities whereas introverted older adults may be more likely than extraverted older adults to manifest their religiosity privately (e.g., by praying at home and watching and listening to religious-based television and radio programs). Involvement in church-related activities, in turn, is a strong predictor of volunteering (Bekkers, 2005;Okun, 1993;Wilson & Musick, 1997, 1999. Two factors contribute to the strong association between involvement in church-related activities and volunteering.…”
Section: Church Attendancementioning
confidence: 99%
See 1 more Smart Citation
“…Ово је случај и када су у питању истраживања корелације између особина личности и волонтерског понашања (Elshaug & Metzer, 2001;Spangler & Reynolds, 1991;Bekkers, 2005;Jabari, Boroujerdi, Ghaeini, Abdollahi & Karimi, 2012). Једно могуће објашњење за такве налазе јесте да особине у узајам-ној интеракцији удружено утичу на мотиве, који су, у каузалном смислу, бли-скији исходима у социјалном понашању (Carlo et al, 2005).…”
unclassified